Reduced Fuzzy Recursive Least-Squares Algorithm For Real Time Estimation - Cheah, Kah Wai (2018)
Adaptive filtering is an online signal processing application that is capable of estimating parameters for the characterization of a real time system. The estimation is done based on the mean-square error (MSE) minimization of the difference between some desired output and the output of the adaptive filter. The unknown transfer function is assumed to be a known structure and is realized by three different structures which are commonly used in conventional adaptive filtering: (i) the finite-duration impulse response (FIR) filter, (ii) the infinite-duration impulse response (IIR) filter, and (iii) the nonlinear filter.